Pengaruh Kualitas Pelayanan, Saluran Distribusi, dan Promosi Terhadap Keputusan Pembelian Logam Mulia : Pada PT. Pegadaian Di Jakarta - Sylvia Kartika Dhamayanti (Prisani Cendekia, 2023)
This study aims to examine and analyze the effect of service quality, distribution channels and promotions on metal purchasing decisions starting at PT. Pawnshop. The sample of this research is Pawnshop customers in DKI Jakarta who have purchased precious metals at least once. The calculation of the number of samples to be studied uses the unknown population formula, the calculation results produce 100 respondents who must be taken so that the research results represent the population. Data was collected using a Likert scale questionnaire, the collected data was analyzed using a Structural Equation Model (SEM) with the SmartPlS version 3.0 analysis tool. The results showed that service quality had a positive and significant effect on purchasing decisions, distribution channels did not significantly influence purchasing decisions, promotion had a positive and significant effect on purchasing decisions